Investigating Ramadan Like Fasting Effects on the Gut Microbiome in BALB/c Mice - Su, Junhong; Li, Fanglin; Wang, Yueying; Su, Yuxin; Verhaar, Auke; Ma, Zhongren; Peppelenbosch, Maikel P. (Frontiers in Nutrition, 2022)
Recently we reported that in healthy volunteer Ramadan-associated intermittent fasting (RAIF) remodels the gut microbiome and resulted in an increase in small chain fatty acid (SFCA)-producing bacteria concomitant with improved metabolic parameters. As interpretation of these results is hampered by the possible psychological effects associated with the study, we now aim to investigate RAIF in experimental animals. To this end, six-week male BALB/c mice were subjected to RAIF (30 days of a 16-hour daily fasting; n = 8) or provided with feed ad libitum (n = 6). Fecal samples were collected before and the end of fasting and bacterial 16S rRNA sequencing was performed. We found that RAIF remodeled the composition of gut microbiota in BALB/c mice (p < 0.01) and especially provoked upregulation of butyrate acid-producing Lachnospireceae and Ruminococcaceae (p < 0.01), resembling the effects seen in human volunteers. Hence we conclude that the effects of RAIF on gut microbiome relate to the timing of food intake and are not likely related to psychological factors possibly at play during Ramadan.